2005
DOI: 10.1016/j.clpt.2005.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Higher exposure to mycophenolic acid with sirolimus than with cyclosporine cotreatment

Abstract: These data show that exposure to mycophenolic acid is higher in patients cotreated with sirolimus than in those cotreated with cyclosporine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…As a result of the gradual increase in MPA exposure, a subset of patients will be above the target window with standard MMF doses of 1000 mg twice daily after 6 to 12 mo after transplantation. This is most likely in patients who are no longer treated with cyclosporine and who have good renal function, albumin level, and hemoglobin (41). The increased MPA exposure may be very welcome in regimens in which cyclosporine is tapered or stopped, and in patients who tolerate such levels without toxicity, dose reductions may not be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the gradual increase in MPA exposure, a subset of patients will be above the target window with standard MMF doses of 1000 mg twice daily after 6 to 12 mo after transplantation. This is most likely in patients who are no longer treated with cyclosporine and who have good renal function, albumin level, and hemoglobin (41). The increased MPA exposure may be very welcome in regimens in which cyclosporine is tapered or stopped, and in patients who tolerate such levels without toxicity, dose reductions may not be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed that dose-corrected MPA exposure is significantly lower in patients treated with a combination of MMF and cyclosporine than in patients receiving MMF alone or in combination with tacrolimus or sirolimus. 151,[154][155][156][157][158][159][160][161][162] This is due to a reduced enterohepatic recirculation of MPA/MPAG in cyclosporine-treated patients, secondary to an inhibition of the MRP2-mediated biliary secretion of MPAG. 154,[215][216][217] Importantly, recent data show that there is an inverse correlation between cyclosporine dose and/or exposure and MPA exposure, 136,147,218 suggesting that MRP2 inhibition by cyclosporine is dose/exposure related.…”
Section: Drug-drug Interactions With Concomitant Immunosuppressive Mementioning
confidence: 95%
“…Coadministration of MMF with cyclosporine decreases exposure to MPA and increases plasma levels of MPAG compared to patients treated with MMF plus tacrolimus or sirolimus or corticosteroids in adults and children (5,6,30,(42)(43)(44)(45)(46)(47).…”
Section: Mmf Metabolism and Pharmacokineticsmentioning
confidence: 99%